Buruh Angkut dan Keluarga Nelayan di Pelabuhan Muara Angke - R.A. Nidha Nadia (Universitas Gadjah Mada, 2016)
This research examines the social interaction amongst the fishers and the porters in the Muara Angke region. Muara Angke is a region which is on the north coast of Jakarta. Due to its fisheries potential, fishing activity has become the main livelihood of the people there. In 1977, the concentration of Jakarta’s fishing activity in the region has made it the center of traditional fishery in Jakarta. Yet, the concentration of fishing activity conducted in Muara Angke failed to provide economic improvement and most people remain under the poverty line. The root of poverty Muara Angke’s fishery community were multidimensional involving social, economic, and political aspects.